Recontextualizing Qur’anic Pedagogy to Address Attention Crisis in Madrasah Ibtidaiyah - Awan Setiawan; Dadang Muslim; Kusmana Kusmana; Cecep Nasrul Yakin (Mandalika Institute, 2026)
The development of the digital era has significantly influenced the learning attention patterns of Madrasah Ibtidaiyah students, particularly in Islamic Religious Education learning. The dominance of visual media, rapid information flow, and the culture of instant learning have increasingly reduced students’ ability to sustain attention in learning activities requiring deep concentration and reflection, including in Al-Qur’an Hadith learning. This study aims to analyze the attention crisis among Madrasah Ibtidaiyah students and reconstruct the relevance of Qur’anic pedagogy in responding to the changing learning attention patterns of the digital generation. While previous studies have primarily focused on the integration of educational technology and digital learning media in Islamic education, limited attention has been given to the relevance of Qur’anic pedagogy in addressing students’ attention crisis. This study fills that gap by recontextualizing Qur’anic pedagogical values as a framework for responding to changing attention patterns in the digital era. The study employed a qualitative approach using library research combined with limited field data obtained through semi-structured interviews with a fifth-grade Al-Qur’an Hadith teacher at Madrasah Ibtidaiyah Persis Burungayun, Garut Regency, Indonesia. Data were analyzed using a descriptive-analytical method through a thematic interpretation (maudhu’i) approach. The findings indicate that students experience difficulties in maintaining attention during verbalistic learning and mechanical memorization activities, yet respond more positively to visual, dialogical, and interactive learning approaches. The study reveals that Qur’anic pedagogy emphasizes not only knowledge transfer but also attention, reflection, internalization, and meaningful engagement. The novelty of this study lies in its integration of Qur’anic pedagogical principles with contemporary attention-crisis discourse, offering a reflective, participatory, and meaningful learning framework for Madrasah Ibtidaiyah students in the digital era.